Factors Influencing Midwives’ Compliance with Immediate Postpartum Monitoring Protocols in Selected Health Facilities in the Greater Accra Region - Attipoe, J. S. K. (University of Ghana, 2025)
Cases of maternal mortality in the Ghanaian context typically occur during the immediate postpartum period, despite strong evidence to support that strict adherence to immediate postpartum monitoring (IPPM) guidelines can significantly improve the health outcomes of both mothers and their newborns. This research evaluated factors influencing the compliance levels of Ghanaian midwives to IPPM protocols. An analytical cross-sectional study design was conducted using five selected health facilities in the Greater Accra Region, comprising two tertiary, two secondary and one primary health care facilities. Following informed consent of participants, midwives who were actively working in the labour and postnatal wards or had a minimum of six months’ experience in maternity care were included in the study. Multistage and random sampling techniques were used to select 426 midwives who met the inclusion criteria across the selected health facilities. A structured questionnaire was used to capture midwives' sociodemographic and facility-based characteristics while a standardized IPPM checklist was used to observe specific practices followed by midwives during the immediate postpartum period. The results revealed that 202 (47.4%) midwives demonstrated total compliance with IPPM protocols while 224 (52.6%) demonstrated partial compliance. In terms of midwives’ individual characteristics, it is showed that midwives in the 26 – 35 age group (odds ratio (OR) = 0.43) and those older than 35 years old (OR= 0.53) were less likely to comply with IPPM protocols (p= 0.001 and p= 0.028 respectively). Also, staff midwives who were recruited as SSM were found to be 6.88 times more likely to adhere to IPPM protocols compared to those recruited at a lower grade at the time of study. Also, increase in gross monthly income was attributed to lower IPPM compliance [3001 – 4000 (OR= 0.36, p= 0.000), 4001 – 5000 (OR= 0.38, p= 0.002) and more than 5000 (odds ratio= 0.47, p= 0.053)]. In terms of facility-based metrics, increased number of midwives during shifts (3 – 5 midwives) and the use of nurses’ notes (OR= 3.17, CI= 1.51 – 7.13) as the preferred IPPM tool were associated with increased compliance (odds ratio= 1.29, p= 0.223). However, the lack of frequent supervision led to lower compliance (OR= 0.41, CI= 0.21 - 0.74). Finally, midwives’ IPMM compliance was highest within primary facilities and least in tertiary facilities. These findings suggest a clear need for improvement in the delivery of postpartum care by Ghanaian-based midwives, particularly in the postpartum period.
Msc. Clinical Trials
Keywords: maternal mortality; postpartum monitoring (IPPM); Greater Accra Region; midwives